2015
DOI: 10.1016/j.jom.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Perceived versus actual value of product substitution flexibility: An experimental investigation

Abstract: Prior literature suggests that in the presence of operational uncertainties such as uncertain demand, firms should deploy operational flexibilities. However, these flexibilities are costly to develop and a correct valuation of these capabilities is necessary to ensure that they are only deployed when the expected benefits exceed the cost.Using a set of behavioral decision-making experiments for inventory of substitutable products, we investigate how decision-makers perform when estimating the value of operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…We refer interested readers to Malhotra and Mackelprang (2012) for a review of the supply chain flexibility literature. While several researchers have looked at the effect of information sharing, lead time, training, production smoothing, coordination, and individual behavioral traits on BWE, very few manufacturing flexibility-oriented studies, with the exception of Bansal and Moritz (2015), have utilized behavioral research using lab or field experiments. They showed that participants usually overestimate the value of flexibility when applied to product substitutions in a behavioral experiment setting.…”
Section: Flexibility Within and Across Firmsmentioning
confidence: 99%
“…We refer interested readers to Malhotra and Mackelprang (2012) for a review of the supply chain flexibility literature. While several researchers have looked at the effect of information sharing, lead time, training, production smoothing, coordination, and individual behavioral traits on BWE, very few manufacturing flexibility-oriented studies, with the exception of Bansal and Moritz (2015), have utilized behavioral research using lab or field experiments. They showed that participants usually overestimate the value of flexibility when applied to product substitutions in a behavioral experiment setting.…”
Section: Flexibility Within and Across Firmsmentioning
confidence: 99%
“…Among studies on capacity management, a nascent research stream is behavioral issues in allocating capacity. Examples of articles in this research stream include capacity management in the assignment of arriving jobs with fairness concerns (Geng, Huh, & Nagarajan, ), retailer's perception bias while experiencing supply shortage (Chen & Zhao, ), and overestimation of monetary value of substituting products in the presence of demand and operational uncertainties (Bansal & Moritz, ). Other examples are focused more on supply‐side dynamics, and include studies of supplier capacity allocation to customers with past recollection of service capacity (Adelman & Mersereau, ), supplier behavior under capacity investment competition (Hu, Wan, Ye, & Chi, ), and bounded rationality among supply chain members in allocating capacity (Chen, Su, & Zhao, ).…”
Section: Literature Classification Based On Operations Contextsmentioning
confidence: 99%
“…Bansal and Moritz (2015) examine the behavioral aspects of estimating the value of product substitution and find that subjects systematically overestimate the monetary value of substitution. Bansal and Moritz (2015) examine the behavioral aspects of estimating the value of product substitution and find that subjects systematically overestimate the monetary value of substitution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our paper is also related to studies of product substitution. Bansal and Moritz (2015) examine the behavioral aspects of estimating the value of product substitution and find that subjects systematically overestimate the monetary value of substitution. Wan et al (2018) investigate consumer behavior in the context of multistore multiproduct substitution with the nested logit model and exogenous substitution model, and estimate substitution probabilities with aggregate sales data.…”
Section: Literature Reviewmentioning
confidence: 99%